2023
DOI: 10.3390/ani13040577
|View full text |Cite
|
Sign up to set email alerts
|

Citric Acid and Magnolol Ameliorate Clostridium perfringens Challenge in Broiler Chickens

Abstract: Clostridium perfringens (C. perfringens) is a common pathogenic bacterium implicated in the enteric diseases of animals. Each year, the disease is responsible for billions of dollars of losses worldwide. The development of new phytomedicines as alternatives to antibiotics is becoming a new hotspot for treating such diseases. Citric acid (CA) and magnolol (MA) have been shown to have antibacterial, antioxidant, and growth-promoting properties. Here, the bacteriostatic effects of combinations of CA and MA agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…An increase in serum immunoglobulin levels is a clear indication of the enhanced innate immunity of animals, with IgG and IgM being the primary immunoglobulins that protect against pathogen invasion into the bloodstream and promote disease resistance [ 40 ]. Our findings corroborated studies conducted by Ding et al [ 41 ] in broiler chickens and Huang et al [ 42 ] in Nile tilapia ( Oreochromis niloticus ), demonstrating that dietary supplementation with magnolol significantly increases serum levels of IgG and IgM. Previous studies have also demonstrated that IgM production is dependent on ALB as its primary substrate [ 43 ], and an increase in both ALB and TP levels has been associated with enhanced innate immunity [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…An increase in serum immunoglobulin levels is a clear indication of the enhanced innate immunity of animals, with IgG and IgM being the primary immunoglobulins that protect against pathogen invasion into the bloodstream and promote disease resistance [ 40 ]. Our findings corroborated studies conducted by Ding et al [ 41 ] in broiler chickens and Huang et al [ 42 ] in Nile tilapia ( Oreochromis niloticus ), demonstrating that dietary supplementation with magnolol significantly increases serum levels of IgG and IgM. Previous studies have also demonstrated that IgM production is dependent on ALB as its primary substrate [ 43 ], and an increase in both ALB and TP levels has been associated with enhanced innate immunity [ 44 , 45 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, certain bioactive substances can indicate the degree of intestinal damage. Serum DAO, endotoxin ( LPS ), and D-LA are prevalently present at low levels in the blood and may enter the circulation only when the intestinal mucosa is damaged; therefore, they can be used as a sensitive indicator of injury in the intestinal stress response ( Ding et al, 2023 ). There was a significant increase in the serum levels of D-LA and DAO at 21 d after Eimeria coccidia infection, which is consistent with the findings from Liu et al (2022) .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study indicate that CA increased the expression of IFN-β and ISG15 in IEC-6 infected with H9N2 and hindered the replication of the influenza virus infection. It has been demonstrated that CA has the capability to improve antioxidant capacity by enhancing the Nrf-2/HO1 pathway [51]. Additionally, 5-Aminolevulinic acid (5-ALA) and sodium ferrous citrate (5-ALA/SFC) induce HO-1 to reduce the cytokine storm induced by SARS-CoV-2 infection to a certain extent [52].…”
Section: Discussionmentioning
confidence: 99%